Dakar Niño under global warming investigated by a high-resolution regionally coupled model - S. Koseki; S. Koseki; R. Vázquez; R. Vázquez; W. Cabos; C. Gutiérrez; D. V. Sein; D. V. Sein; D. V. Sein; M.-L. Bachèlery; M.-L. Bachèlery; M.-L. Bachèlery (Earth System Dynamics)
In this study, we investigated interannual variability in sea surface temperature (SST) along the northwestern African coast, focusing on strong Dakar Niño and Niña events and their potential alterations under the RCP8.5 emission scenario for global warming, using a high-resolution regional coupled model. Our model accurately reproduces the SST seasonal cycle along the northwestern African coast, including its interannual variability in terms of amplitude, timing, and the position of maximum variability. Comparing Dakar Niño variability between the 1980–2010 and 2069–2099 periods, we found that it intensifies under a warmer climate without changing its location and timing. The intensification is more pronounced during Dakar Niñas (cold SST events) than during Dakar Niños (warm SST events). In the future, SST variability will be correlated with ocean temperature and vertical motion at deeper layers. The increase in Dakar Niño variability can be explained by the larger variability in meridional wind stresses, which is likely to be amplified in the future by enhanced land–sea thermal contrast and associated sea-level-pressure anomalies extending from the Iberian Mediterranean area. A heat budget analysis of the mixed layer suggests that surface heat flux and horizontal-advection anomalies are comparably important for Dakar Niño and Niña events in the present climate. However, the future intensification of Dakar Niños and Niñas is likely to be driven by surface heat flux (latent heat flux and shortwave radiation). While horizontal- and vertical-advection anomalies also contribute to the intensification, their roles are secondary.